Empowerment of Islamic Society Through Economic and Social Programs for Economic Welfare in Sidoharjo Village, Pringsewu Regency, Lampung - Fariza Makmum; Imanudin Imanudin; Dian Ferdiansyah; Adi Shambono (Departement of Mathematics Education, 2025)
The purpose of the study was to analyze the empowerment of the Islamic community through economic and social programs for economic welfare in Sidoharjo Village, Pringsewu Regency, Lampung. The research method used qualitative research with a case study type. The subjects of the study were the Muslim community involved in the empowerment program, including program beneficiaries, program managers and local community leaders. Data collection used observation, interviews, and documentation. Data analysis adopted the Robert Yin model by making an explanation, which includes (1) making a theoretical statement/initial proposition about social policy/behavior; (2) comparing initial case findings with statements/propositions; (3) improving statements; (4) comparing improvements with existing facts; (5) repeating the process as many times as necessary . The results of the study showed that the Islamic community empowerment program in Sidoharjo Village succeeded in improving the economic welfare of the community. Through skills training, such as entrepreneurship and information technology, many residents were able to open small businesses, increase income, and reduce dependence on the agricultural sector. Women's empowerment has also increased, with many women actively participating in economic activities. Despite challenges in accessing capital and information, the program has had significant positive impacts, creating new jobs, and encouraging community participation in decision-making. Overall, the program has succeeded in optimizing local potential and improving the quality of life of the community in Sidoharjo Village.